Pengaruh Startegi Pemasaran Terhadap Peningkatan Penjualan Produk Ikan Kaleng Isabella pada PT.Sinar Purefoods Internasional Bitung - Sairo, Hesti; Sumampouw, Harry J.; Walangitan, Olivia (JURNAL ADMINISTRASI BISNIS (JAB), 2018)
In line with the rapid development of science and technology that experienced an increase and change over time brings logical consequences for the business world by shifting the values of the demands of human needs and wants. Where the products / services produced are expected to be well received by consumers. Customer’s satisfaction is an important thing in the success of marketing products / services. Consumer satisfaction is determined by many factors such as marketing strategy the attention of researchers with the assumption that if a good marketing strategy it will make consumers satisfied. The researcher aims to know how far the marketing strategy to increase selling of Isabella canned fish products at PT. Sinar Purefoods International Bitung by taking the respondents as much as 70 respondents. The method of analysis used in this study is a quantitative method with a simple correlation analysis approach and simple regression. The result of simple correlation analysis is r = 0,05 this indicate that if marketing strategy go up hence increase of sale will go up also. The degree of correlation is in the "high" category and after testing the significance of "very significant" evidently. With the coefficient of determination factor marketing strategy is determined by the factor of increase in sales and the rest is determined by other factors. With a simple regression analysis can be interpreted that any addition of a scale on the marketing strategy will lead to an increase in sales increase. Thus it is evident that the marketing strategy has an influence on the increase in sales. Based on the results of this study, researchers suggest that leaders continue to observe and pay attention to the elements of marketing strategy variables that have not been touched in the research and to keep the current marketing strategy to provide increased sales to the company.